Integration of Arabic Language on Social Interaction in Patani Southern Thailand - Syarafina, Dea Agta; Muhajir; Amy Fitriani Siregar; Saariah; Ahmad Suhendra Hasibuan (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
This research aims to analyze the integration of Arabic in the daily life of the Patani people, focusing on the existence factor of Fathoni University as a center of Islamic education in Southern Thailand. This research uses a descriptive qualitative method with a literature study, including a review of literature related to the use of Arabic in many aspects in Patani. The results of this study show that Arabic plays an important role as a communication tool in religious, educational, and cultural contexts for the people of Patani. The integration of Arabic in the daily life of the Patani people through three main aspects: religious practices, educational institutions, and socio-cultural environments, with particular attention to the role of Fathoni University as a key facilitator. While the Arabic language has also greatly influenced the religious terms of the Patani Malay language, which is part of the local cultural identity; the research also identified several challenges, including the dominance of the Thai language and limited Arabic language skills among the community. The research underscores the importance of a sustainable educational strategy to strengthen the position of Arabic as an important element in the religious and cultural identity of the Patani people.